A method for preparing a nanoscale sulfide solid-state electrolyte
Patent Information
- Application Number
- CN202511810370.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-03
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-12-03
AI Technical Summary
常规干法球磨通常可将电解质粉末细化至1μm左右,但继续球磨降低粒径将会导致团聚现象严重,难以进一步纳米化
[0020] This invention utilizes a low-temperature cryogenic wet ball milling process to achieve sustained particle refinement of sulfide electrolytes under continuous low-temperature conditions. This effectively prevents thermal instability reactions during continuous ball milling, maintains the chemical stability of the electrolyte, and significantly reduces the particle size of the sulfide electrolyte to the nanoscale. This enhances the interfacial contact and compactness of the electrolyte while still maintaining excellent ionic conductivity (up to 10). -3 S·cm -1 (Level). Furthermore, the preparation method provided by this invention is simple, scalable, and applicable to all sulfide electrolyte systems.
Smart Images

Figure CN121317766B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of all-solid-state electrolyte material preparation technology, and particularly relates to a method for preparing a nanoscale sulfide solid electrolyte. Background Technology
[0002] Sulfide solid electrolytes (such as Li) 10 GeP2S 12 Sulfide electrolytes (such as Li6PS5Cl and Li3PS4) are considered the most promising solid electrolytes for all-solid-state batteries (ASSBs) due to their high ionic conductivity, good interfacial contact, and excellent film-forming properties. The particle size of sulfide electrolyte powder significantly affects its electrochemical performance. Generally, reducing the particle size can significantly increase the specific surface area and ion transport pathways, improve interfacial contact, and reduce interfacial impedance. More importantly, electrolyte nano-sizing is a necessary approach to improve the energy density of sulfide ASSBs, because nano-sizing can reduce the proportion of sulfide electrolyte in the composite cathode, thereby increasing the energy density of sulfides. Furthermore, in practical applications, electrolyte powder needs to be processed into an electrolyte membrane. Currently, the large particle size of electrolyte powder leads to large gaps between electrolyte membrane particles, easily causing lithium dendrite penetration short circuits. Therefore, nano-sizing of sulfide electrolytes can ensure the compactness of the electrolyte membrane while reducing its thickness, thereby further improving the energy density of all-solid-state batteries.
[0003] In existing technologies, particle refinement of sulfide electrolytes mainly employs dry ball milling or wet ball milling. Conventional dry ball milling can typically refine electrolyte powder to around 1 μm, but further milling to reduce particle size leads to severe agglomeration, making further nano-scale reduction difficult. Conventional wet ball milling, conducted in a liquid medium, can further reduce particle size to the nanoscale, but during prolonged milling, frictional heat generation and continuous temperature increases in the milling jar can easily trigger thermal reactions and structural decomposition of the sulfide electrolyte, leading to electrolyte failure. Therefore, traditional methods struggle to simultaneously achieve both powder refinement and chemical stability.
[0004] Therefore, developing a method for preparing structurally normal and stable nanoscale sulfide electrolytes suitable for large-scale industrial production has become a pressing technical challenge in this field. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention proposes a method for preparing nanoscale sulfide solid electrolytes. This invention utilizes low-temperature cryogenic wet ball milling to achieve effective nano-sized electrolyte powder particles while maintaining electrolyte structural stability, thereby enabling the batch and stable preparation of nanoscale sulfide electrolytes.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] This invention provides a method for preparing nanoscale sulfide solid electrolytes, comprising the following steps:
[0008] (1) The micron-sized sulfide electrolyte and non-polar solvent were mixed and then subjected to low-temperature cryogenic wet ball milling to obtain a slurry;
[0009] (2) The slurry is evaporated, dried and annealed in sequence to obtain the nano-scale sulfide solid electrolyte.
[0010] Further, in step (1), the micron-sized sulfide electrolyte is selected from at least one of Li-PS glass / glass-ceramic electrolyte, thio-LISICON electrolyte and Li-argyrodite electrolyte.
[0011] Furthermore, the Li-PS glass / glass-ceramic electrolyte is selected from 20Li2S-80P2S5 and Li7P3S. 11 and at least one of Li3PS4; the thio-LISICON type electrolyte is selected from Li 10 SnP2S 12 and / or Li 10 GeP2S 12 The Li-argyrodite type electrolyte is selected from Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 Li6PS5Br, Li6PS5I, Li 10 Si 0.3 PS 6.7 Cl 1.8 and Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 At least one of them.
[0012] Further, in step (1), the nonpolar solvent is selected from toluene, xylene, n-hexane or cyclohexane.
[0013] Further, in step (1), the temperature of the low-temperature cryogenic wet ball milling is -20℃ to -80℃, and the time of the low-temperature cryogenic wet ball milling is 30 to 80 hours; the cryogenic agent of the low-temperature cryogenic wet ball milling is selected from liquid nitrogen or ethanol.
[0014] Further, in step (1), the ball-to-material mass ratio of the low-temperature cryogenic wet ball mill is (20~80):1, and the rotation speed of the low-temperature cryogenic wet ball mill is 300~800 rpm.
[0015] Furthermore, in step (2), the evaporation temperature is 40~60℃.
[0016] Furthermore, in step (2), the drying temperature is 50~90℃ and the drying time is 1~4h.
[0017] Furthermore, in step (2), the annealing temperature is 180~250℃ and the annealing time is 2~4h.
[0018] The present invention also provides a nanoscale sulfide solid electrolyte prepared by the preparation method described above, wherein the particle size of the nanoscale sulfide solid electrolyte is 50~500nm.
[0019] Compared with the prior art, the present invention has the following advantages and technical effects:
[0020] This invention utilizes a low-temperature cryogenic wet ball milling process to achieve sustained particle refinement of sulfide electrolytes under continuous low-temperature conditions. This effectively prevents thermal instability reactions during continuous ball milling, maintains the chemical stability of the electrolyte, and significantly reduces the particle size of the sulfide electrolyte to the nanoscale. This enhances the interfacial contact and compactness of the electrolyte while still maintaining excellent ionic conductivity (up to 10). -3 S·cm -1 (Level). Furthermore, the preparation method provided by this invention is simple, scalable, and applicable to all sulfide electrolyte systems. Attached Figure Description
[0021] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:
[0022] Figure 1 For example, the micron-sized Li in Example 1 10 Si 0.3 PS 6.7 Cl 1.8 Electrolytes and nanoscale Li 10 Si 0.3 PS 6.7 Cl 1.8 X-ray diffraction patterns of electrolytes, in which LiSiPSCl-pre-cryo-ball-milled micron-sized Li 10 Si 0.3 PS 6.7 Cl 1.8 Electrolyte, LiSiPSCl - Low-temperature cryogenic ball milling refers to nano-sized Li 10 Si 0.3 PS 6.7 Cl 1.8 Electrolytes;
[0023] Figure 2 Nanoscale Li prepared for Comparative Example 1 10 Si 0.3 PS 6.7 Cl 1.8 X-ray diffraction pattern (left) and impedance spectrum (right) of electrolyte;
[0024] Figure 3 For example, the micron-sized Li in Example 2 10 Si 0.3 PS 6.7 Cl 1.8 Electrolytes and nanoscale Li 10 Si 0.3 PS 6.7 Cl 1.8 Comparison of AC impedance spectra of electrolytes, where LiSiPSCl-before cryogenic ball milling indicates micron-sized Li. 10 Si 0.3 PS 6.7 Cl 1.8 Electrolyte, LiSiPSCl - Low-temperature cryogenic ball milling refers to nano-sized Li 10 Si 0.3 PS 6.7 Cl 1.8 Electrolytes;
[0025] Figure 4 For example, the micron-sized Li in Example 3 10 Si 0.3 PS 6.7 Cl 1.8 Electrolyte (left) and nanoscale Li 10 Si 0.3 PS 6.7 Cl 1.8 SEM image of the electrolyte (right);
[0026] Figure 5 Li prepared in Examples 1-5 and Comparative Example 1 10 Si 0.3 PS 6.7 Cl 1.8 Electrolyte particle size distribution diagram. Detailed Implementation
[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0029] This invention provides a method for preparing a nanoscale sulfide solid electrolyte, comprising the following steps:
[0030] (1) The micron-sized sulfide electrolyte and non-polar solvent were mixed and then subjected to low-temperature cryogenic wet ball milling to obtain a slurry;
[0031] (2) The slurry is evaporated, dried and annealed in sequence to obtain the nano-scale sulfide solid electrolyte.
[0032] In a preferred embodiment, in step (1), the micron-sized sulfide electrolyte is selected from at least one of Li-PS glass / glass-ceramic electrolyte, thio-LISICON electrolyte, and Li-argyrodite electrolyte.
[0033] In a preferred embodiment, the Li-PS glass / glass-ceramic electrolyte is selected from 20Li2S-80P2S5 and Li7P3S. 11 and at least one of Li3PS4; the thio-LISICON type electrolyte is selected from Li 10 SnP2S 12 and / or Li 10 GeP2S 12 The Li-argyrodite type electrolyte is selected from Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 Li6PS5Br, Li6PS5I, Li 10 Si 0.3 PS 6.7 Cl 1.8 and Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 At least one of them.
[0034] In a preferred embodiment, in step (1), the particle size of the micron-sized sulfide electrolyte is 5-50 μm.
[0035] In a preferred embodiment, in step (1), the nonpolar solvent is selected from toluene, xylene, n-hexane, or cyclohexane, and more preferably toluene and cyclohexane. This invention uses a nonpolar solvent that does not react with the sulfide electrolyte, thus avoiding changes in the composition of the sulfide electrolyte.
[0036] In a preferred embodiment, in step (1), the temperature of the low-temperature cryogenic wet ball milling is -20℃ to -80℃, more preferably -30℃ to -60℃; the time of the low-temperature cryogenic wet ball milling is 30 to 80 hours, more preferably 30 to 50 hours; the refrigerant for the low-temperature cryogenic wet ball milling is selected from liquid nitrogen or ethanol. If the ball milling temperature is too high, the electrolyte is prone to reaction during the milling process, affecting the stability of the electrolyte structure; although the longer the milling time, the smaller the particle size of the electrolyte, prolonged contact between the electrolyte and the solvent will affect the stability of the electrolyte structure.
[0037] In a preferred embodiment, in step (1), the ball-to-material mass ratio in the cryogenic wet ball mill is (20~80):1, more preferably (30~60):1; the rotation speed of the cryogenic wet ball mill is 300~800 rpm, more preferably 400~600 rpm; and the grinding balls used in the cryogenic wet ball mill are selected from zirconia grinding beads. During the ball milling process, although a larger ball-to-material mass ratio results in finer grinding of the electrolyte, ineffective ball-beating occurs, and costs are increased.
[0038] In a preferred embodiment, step (1) specifically involves: loading a micron-sized sulfide electrolyte into a ball mill jar with an internal cavity in a glove box, adding a non-polar solvent and grinding balls, and then vacuum sealing the ball mill jar; loading the sealed ball mill jar into a ball mill, adding a refrigerant into the internal cavity of the ball mill jar, controlling the temperature of the jar through an external cooling circulation system, and then starting the ball mill for low-temperature cryogenic wet ball milling to obtain a slurry.
[0039] In a preferred embodiment, in step (2), the evaporation temperature is 40~60°C; the evaporation is carried out under vacuum conditions. This invention removes solvents through evaporation.
[0040] In a preferred embodiment, in step (2), the drying temperature is 50~90℃, more preferably 60~80℃; the drying time is 1~4h, more preferably 2~3h; and the drying is carried out under an inert atmosphere.
[0041] In a preferred embodiment, in step (2), the annealing temperature is 180~250℃, more preferably 200~240℃; the annealing time is 2~4h; and the annealing is performed under vacuum. This invention improves the crystallinity and ionic conductivity of the electrolyte through annealing.
[0042] The present invention also provides a nanoscale sulfide solid electrolyte prepared by the preparation method described above, wherein the particle size of the nanoscale sulfide solid electrolyte is 50~500nm, more preferably 184~303nm.
[0043] Unless otherwise specified, all raw materials used in the embodiments of this invention were purchased through commercial channels.
[0044] Example 1
[0045] A method for preparing a nanoscale sulfide solid electrolyte, comprising the following steps:
[0046] (1) Micron-sized Li in a glove box 10 Si 0.3 PS 6.7 Cl 1.8 The electrolyte is loaded into a cryogenic ball mill jar with an internal cavity, and then toluene and zirconium oxide ball mill beads are added at a ball-to-material mass ratio of 30:1. The ball mill jar is then vacuum sealed.
[0047] (2) Place the sealed ball mill jar into the ball mill, add liquid nitrogen into the internal cavity of the ball mill jar, control the temperature of the jar at -50℃ through the external cooling circulation system, maintain a constant temperature, start the ball mill and continuously ball mill at a speed of 500rpm for 30h to obtain slurry;
[0048] (3) The obtained slurry was transferred to a glove box, and the solvent was evaporated at 40°C to remove it. Then it was dried at 60°C for 4 hours, followed by vacuum annealing at 200°C for 2 hours to obtain nano-sized Li. 10 Si 0.3 PS 6.7 Cl 1.8 Electrolytes.
[0049] Comparative Example 1 (Conventional Wet Ball Milling Method)
[0050] A method for preparing a nanoscale sulfide solid electrolyte, comprising the following steps:
[0051] Steps (1) and (3) are the same as in Example 1;
[0052] Step (2) is as follows: the sealed ball mill jar is loaded into the planetary ball mill, the ball mill is started and continuously ball milled at a speed of 500 rpm for 30 hours to obtain slurry.
[0053] Example 2
[0054] A method for preparing a nanoscale sulfide solid electrolyte, comprising the following steps:
[0055] (1) Micron-sized Li in a glove box 10 Si 0.3 PS 6.7 Cl 1.8The electrolyte is loaded into a cryogenic ball milling jar with an internal cavity, and then cyclohexane and zirconium oxide ball milling beads are added with a ball-to-material mass ratio of 40:1. The ball milling jar is then vacuum sealed.
[0056] (2) Place the sealed ball mill jar into the ball mill, add liquid nitrogen into the internal cavity of the ball mill jar, control the temperature of the jar at -50℃ through the external cooling circulation system, maintain a constant temperature, start the ball mill and continuously ball mill at a speed of 550rpm for 30h to obtain slurry;
[0057] (3) The obtained slurry was transferred to a glove box, and the solvent was removed by evaporation at 40°C. Then it was dried at 80°C for 2 hours, followed by vacuum annealing at 220°C for 2 hours to obtain nano-sized Li. 10 Si 0.3 PS 6.7 Cl 1.8 Electrolytes.
[0058] Example 3
[0059] A method for preparing a nanoscale sulfide solid electrolyte, comprising the following steps:
[0060] (1) Micron-sized Li in a glove box 10 Si 0.3 PS 6.7 Cl 1.8 Electrolyte is loaded into a cryogenic ball mill jar with an internal cavity, and then hexane and zirconium oxide ball mill beads are added at a ball-to-material mass ratio of 50:1. The ball mill jar is then vacuum sealed.
[0061] (2) Place the sealed ball mill jar into the ball mill, add ethanol into the internal cavity of the ball mill jar, control the temperature of the jar at -40℃ through the external cooling circulation system to maintain a constant temperature, start the ball mill and continuously ball mill at a speed of 550rpm for 40h to obtain slurry;
[0062] (3) The obtained slurry was transferred to a glove box, and the solvent was evaporated at 50°C to remove it. Then it was dried at 80°C for 4 hours, followed by vacuum annealing at 240°C for 4 hours to obtain nano-sized Li. 10 Si 0.3 PS 6.7 Cl 1.8 Electrolytes.
[0063] Example 4
[0064] A method for preparing a nanoscale sulfide solid electrolyte, comprising the following steps:
[0065] (1) Micron-sized Li in a glove box 10 GeP2S 12The electrolyte is loaded into a cryogenic ball mill jar with an internal cavity, and then toluene and zirconium oxide ball mill beads are added at a ball-to-material mass ratio of 40:1. The ball mill jar is then vacuum sealed.
[0066] (2) Place the sealed ball mill jar into the ball mill, add ethanol into the internal cavity of the ball mill jar, control the temperature of the jar at -40℃ through the external cooling circulation system to maintain a constant temperature, start the ball mill and continuously ball mill at a speed of 500 rpm for 30 hours to obtain slurry;
[0067] (3) The obtained slurry was transferred to a glove box, the solvent was evaporated at 40°C, dried at 80°C for 2 hours, and then vacuum annealed at 240°C for 3 hours to obtain nano-sized Li. 10 GeP2S 12 Electrolytes.
[0068] Example 5
[0069] A method for preparing a nanoscale sulfide solid electrolyte, comprising the following steps:
[0070] (1) Micron-sized Li7P3S in a glove box 11 The electrolyte is loaded into a cryogenic ball milling jar with an internal cavity, and then toluene and zirconium oxide ball milling beads are added at a ball-to-material mass ratio of 50:1. The ball milling jar is then vacuum sealed.
[0071] (2) Place the sealed ball mill jar into the ball mill, add liquid nitrogen into the internal cavity of the ball mill jar, control the temperature of the jar at -50℃ through the external cooling circulation system, maintain a constant temperature, start the ball mill and continuously ball mill at a speed of 550rpm for 40h to obtain slurry;
[0072] (3) The obtained slurry was transferred to a glove box, and the solvent was evaporated at 40°C to remove it. Then it was dried at 80°C for 2 hours, followed by vacuum annealing at 220°C for 3 hours to obtain nano-sized Li7P3S. 11 Electrolytes.
[0073] Comparative Example 2
[0074] A method for preparing a nanoscale sulfide solid electrolyte differs from Example 1 in that, in step (2), the temperature of the tank is controlled at -10°C by an external cooling circulation system, while the rest is the same as in Example 1.
[0075] Comparative Example 3
[0076] A method for preparing a nanoscale sulfide solid electrolyte differs from Example 1 in that, in step (2), a ball mill is started and continuously ball milled at a speed of 500 rpm for 10 hours to obtain a slurry; the rest is the same as in Example 1.
[0077] Comparative Example 4
[0078] A method for preparing a nanoscale sulfide solid electrolyte differs from Example 1 in that, in step (2), a ball mill is started and continuously ball-milled at a speed of 500 rpm for 80 hours to obtain a slurry; the rest is the same as in Example 1.
[0079] Comparative Example 5
[0080] A method for preparing a nanoscale sulfide solid electrolyte differs from Example 1 in that, in step (3), vacuum annealing is performed at 150°C, while the rest is the same as in Example 1.
[0081] Comparative Example 6
[0082] A method for preparing a nanoscale sulfide solid electrolyte differs from Example 1 in that, in step (3), vacuum annealing is performed at 350°C, while the rest is the same as in Example 1.
[0083] The electrolytes prepared in Examples 1-5 and Comparative Examples 1-6 were subjected to particle size measurement and ionic conductivity testing. The results are shown in Table 1.
[0084] Table 1
[0085]
[0086] As can be seen from Table 1, the Li prepared in Example 1 10 Si 0.3 PS 6.7 Cl 1.8 The ionic conductivity of the electrolyte is 3.3 × 10⁻⁶. -3 S / cm, while the Li prepared in Comparative Example 1 10 Si 0.3 PS 6.7 Cl 1.8 The ionic conductivity of the electrolyte is 1.6 × 10⁻⁶. -5 S / cm indicates that the method of the present invention can achieve the nano-scale formation of sulfide electrolytes while ensuring both high ionic conductivity and stable nanoscale electrolyte structure after ball milling.
[0087] Figure 1 For example, the micron-sized Li in Example 1 10 Si 0.3 PS 6.7 Cl 1.8 Electrolytes and nanoscale Li 10 Si 0.3 PS 6.7 Cl 1.8X-ray diffraction patterns of electrolytes, in which LiSiPSCl-pre-cryo-ball-milled micron-sized Li 10 Si 0.3 PS 6.7 Cl 1.8 Electrolyte, LiSiPSCl - Low-temperature cryogenic ball milling refers to nano-sized Li 10 Si 0.3 PS 6.7 Cl 1.8 Electrolytes. From Figure 1 It can be seen that, compared with micron-sized Li 10 Si 0.3 PS 6.7 Cl 1.8 Compared to electrolytes, the nanoscale Li prepared by the method of this invention... 10 Si 0.3 PS 6.7 Cl 1.8 The electrolyte's crystal structure remained intact and undamaged.
[0088] Figure 2 Nanoscale Li prepared for Comparative Example 1 10 Si 0.3 PS 6.7 Cl 1.8 X-ray diffraction pattern (left) and impedance spectrum (right) of the electrolyte. Figure 2 The X-ray diffraction pattern shows that the electrolyte has reacted and its structure has been completely destroyed after conventional wet ball milling. Figure 2 The impedance spectrum shows that the electrolyte has a very high impedance after conventional wet ball milling, and the ionic conductivity drops sharply.
[0089] Figure 3 For example, the micron-sized Li in Example 2 10 Si 0.3 PS 6.7 Cl 1.8 Electrolytes and nanoscale Li 10 Si 0.3 PS 6.7 Cl 1.8 Comparison of AC impedance spectra of electrolytes, where LiSiPSCl-before cryogenic ball milling indicates micron-sized Li. 10 Si 0.3 PS 6.7 Cl 1.8 Electrolyte, LiSiPSCl - Low-temperature cryogenic ball milling refers to nano-sized Li 10 Si 0.3 PS 6.7 Cl 1.8 Electrolytes. From Figure 3 It can be seen that the method provided by this invention can be used to process Li 10Si 0.3 PS 6.7 Cl 1.8 Even after electrolyte removal, the electrolyte can still maintain good ionic conductivity.
[0090] Figure 4 For example, the micron-sized Li in Example 3 10 Si 0.3 PS 6.7 Cl 1.8 Electrolyte (left) and nanoscale Li 10 Si 0.3 PS 6.7 Cl 1.8 SEM image of the electrolyte (right). From Figure 4 It can be seen that the micron-sized sulfide electrolyte has been successfully nanoscaled after cryogenic ball milling.
[0091] Figure 5 The particle size distribution diagrams are for the sulfide electrolytes prepared in Examples 1-5 and Comparative Example 1. From... Figure 5 It can be seen that the particle size distribution and average particle size of the sulfurized electrolytes prepared in Examples 1-5 and Comparative Example 1 all reached the nanometer level. However, the particle size of the sulfurized electrolyte prepared in Comparative Example 1 is larger than that of the sulfurized electrolytes prepared in Examples 1-5.
[0092] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a nanoscale sulfide solid electrolyte, characterized in that, Includes the following steps: (1) The micron-sized sulfide electrolyte and non-polar solvent were mixed and then subjected to low-temperature cryogenic wet ball milling to obtain a slurry; The ball milling is carried out in a vacuum-sealed ball mill jar; The ball mill jar has an internal cavity, and the low-temperature cryogenic wet ball milling controls the jar temperature by adding a refrigerant to the internal cavity and combining it with an external cooling circulation system. The temperature of the low-temperature cryogenic wet ball milling is -20℃ to -80℃, and the time of the low-temperature cryogenic wet ball milling is 30 to 80 hours; the refrigerant of the low-temperature cryogenic wet ball milling is selected from liquid nitrogen or ethanol. The nonpolar solvent is selected from toluene, xylene, n-hexane, or cyclohexane; The ball-to-material mass ratio of the low-temperature cryogenic wet ball mill is (20~80):1, and the rotation speed of the low-temperature cryogenic wet ball mill is 300~800 rpm; (2) The slurry is sequentially evaporated, dried and annealed to obtain the nano-scale sulfide solid electrolyte; The evaporation temperature is 40~60℃; The drying temperature is 50~90℃, and the drying time is 1~4h; The annealing temperature is 180~250℃, and the annealing time is 2~4h; The particle size of the nanoscale sulfide solid electrolyte is 50~500nm.
2. The preparation method according to claim 1, characterized in that, In step (1), the micron-sized sulfide electrolyte is selected from at least one of Li-PS glass / glass ceramic electrolyte, thio-LISICON electrolyte and Li-argyrodite electrolyte.
3. The preparation method according to claim 2, characterized in that, The Li-PS glass / glass-ceramic electrolyte is selected from 20Li2S-80P2S5 and Li7P3S. 11 and at least one of Li3PS4; the thio-LISICON type electrolyte is selected from Li 10 SnP2S 12 and / or Li 10 GeP2S 12 The Li-argyrodite type electrolyte is selected from Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 Li6PS5Br, Li6PS5I, Li 10 Si 0.3 PS 6.7 Cl 1.8 and Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 At least one of them.
4. A nanoscale sulfide solid electrolyte prepared by the preparation method according to any one of claims 1 to 3, characterized in that, The particle size of the nanoscale sulfide solid electrolyte is 50~500nm.
Citation Information
Patent Citations
Preparation method of sulfide solid electrolyte based on wet ball milling
CN115939501A
Preparation method of submicron sulfide solid electrolyte
CN118173865A